La–Fe magnetic bentonite stimulated denitrifying phosphorus removal from low C/N wastewater in the A2/O process: Performance, microbial community, and potential mechanism. (1st November 2022) - Lu, Xiejuan; Zhong, Zhenxing; Yan, Rui; Zan, Feixiang; Lou, Wei; Liu, Jingjing; Wu, Xiaohui; Zhang, Beiping
Abstract: A novel process combined A 2 /O bioreactor with a millimeter-sized magnetic lanthanum-modified bentonite (La–Fe-MB) granules material (terms as A 2 /O–La–Fe-MB) was proposed for highly efficient phosphorus removal from municipal sewage. A series of experiments were carried out to explore the feasibility and suitability of using La–Fe-MB as a novel adsorbent. The performance of nutrient removal and microbial composition, and any adverse effect brought by dosing La–Fe-MB are of interests. The long-term operation (240 days) suggested that dosing La–Fe-MB in the A 2 /O bioreactor achieved a highly-efficient TP removal with average effluent TP concentrations for 0.22 mg/L by enhancing denitrifying phosphorus removal (DPR) and chemical precipitation. Based on the mass balance equations, La–Fe-MB contributed to ∼39.7% of TP removal via adsorption/precipitation in the anaerobic zone, 43.6% of TP was removed through anoxic DPR in the anoxic zone, and post-aerobic zone further reduced ∼14.4% of phosphorus. Moreover, an interesting synergic effect between the La–Fe-MB and functional bacteria was found in the combined process. La–Fe-MB addition not only have less effect on the removal of organic, nitrogen species, and functional bacteria (AOB, NOB, etc., ), but significantly facilitated the enrichment of denitrifying phosphorus accumulating organisms (DPAOs) via releasing traces of Fe (Fe(II)/Fe(III)) in bioreactor. Besides, DPAOs (1.7%), glycogen accumulating organisms (GAOs) (0.031%) and P-accumulating organisms (PAOs) (0.41%) co-existed in this combined system, potentially resulting in simultaneous denitrifying dephosphatation and aerobic phosphorus absorbing. The above results demonstrated that the novel A 2 /O–La–Fe-MB system is a promising technique for highly-efficient TP removal from wastewater. Graphical abstract: Image 1 Highlights: A2/O–La–Fe-MB system was proposed for highly efficient P removal from wastewater. Additional La–Fe-MB significantly promoted denitrifying phosphorus removal (DPR). In-situ generated Fe2+/Fe3+ enhanced both DPR and chemical Phosphorus removal. La–Fe-MB and DPR contributed to 39.7% and 43.6% of the TP removal, respectively. DPAOs (1.7%), GAOs (0.031%), and PAOs (0.41%) co-existed in the combined system.